Transformative spaces in the making: key lessons from nine cases in the Global South - Pereira, Laura (2019)
Creating a just and sustainable planet will require not only small changes, but also systemic transformations in how humans relate to the planet and to each other, i.e., social–ecological transformations. We suggest there is a need for collaborative environments where experimentation with new configurations of social–ecological systems can occur, and we refer to these as transformative spaces. In this paper, we seek a better understanding of how to design and enable the creation of transformative spaces in a development context. We analyse nine case studies from a previous special issue on Designing Transformative Spaces that aimed to collect examples of cutting-edge action-oriented research on transformations from the Global South. The analysis showed five design phases as being essential: Problem Definition Phase; Operationalisation Phase; Tactical Phase; Outcome Phase; and Reflection Phase. From this synthesis, we distilled five key messages that should be considered when designing research, including: (a) there are ethical dilemmas associated with creating a transformative space in a system; (b) it is important to assess the readiness of the system for change before engaging in it; (c) there is a need to balance between ‘safe’ and ‘safe-enough’ spaces for transformation; (d) convening a transformative space requires an assemblage of diverse methodological frameworks and tools; and (e) transformative spaces can act as a starting point for institutionalising transformative change. Many researchers are now engaging in transdisciplinary transformations research, and are finding themselves at the knowledge–action interface contributing to transformative space-making. We hope that by analysing experiences from across different geographies we can contribute towards better understanding of how to navigate the processes needed for the urgent global transformations that are being called for to create a more equitable and sustainable planet Earth.